L’IMPASSE EPISTEMOLOGICA, LE RELAZIONI DI POTERE E LO STIGMA. ALCUNI APPUNTI SULLA STORIA DELLA PSICHIATRIA - Salottolo, Delio (S&F_scienzaefilosofia.it, 2015)
In this essay, I intend to analyze the epistemological, ontological and sociological complexity of the terms “normal” and “pathological” and of psychiatry tout court as a theoretical and institutional device. While “mental illness” is indeed undefinable, its definition is, nevertheless, critical to understand some aspects of social partitioning in bourgeois and capitalist modernity. Thus, the parallel tracks that I will follow here pertain on one hand to the importance of the definition of the “history of science” and on the other to the ambiguity inherent to the definition of “abnormality” itself. The conflict between facts and values is key not only in terms of scientific definition but also as for the position of the “stigmatized” in relation to the institution, the social body, the self, and within the interaction that is always determined as asymmetrical.